DETECTION OF WIND PROFILE ON TITAN FROM ALMA OBSERVATIONS: LINE PROFILE RETRIEVALS OF HNC, HC3N, CH3CN, AND HCN - Badingah, Luluatul
Titan, Saturn's largest natural satellite, is the only one with a substantial atmosphere in the Solar System. In situ observations of Titan's atmosphere using Huygens probe conrmed three dominated molecules: nitrogen, methane, and hydrogen; and uncovered its vertical thermal prole consisting of: the troposphere, stratosphere, mesosphere and thermosphere. In addition, Titan's atmosphere appears to be very dynamic that is evident from the existence of pole-to-pole one-cell general circulation and hydrocarbon cycle. In regard to its atmospheric dynamics, wind observations can yield the corresponding important information. One of the few methods used to measure wind speed is to measure Doppler shifts from the molecular emission line. Accordingly, HNC, HC3N, CH3CN, and HCN are few examples of molecules that can be used to measure wind speed because of their high abundance in dierent altitude regions. Observations using ALMA radio telescope revealed that the peak emission of HNC, HCN, HC3N, and CH3CN spectra probed altitudes around 990, 745, 710, and 345 km, respectively, and therefore can be used to probe Titan's upper atmosphere. This Final Project analyzes observational data from ALMA, using CASA for data processing, and Simple Linear Regression tting method to determine wind speed values in Titans atmosphere from HNC, HC3N, CH3CN, and HCN spectra. The value of wind speed obtained from this Final Project are 208,594 88,667 m/s for HNC spectra, 234,982 49,954 m/s for HC3N, 251,239 39,790 m/s for CH3CN, and 333,083 67,114 m/s for HCN. Dierences in values from previous work (Lellouch dkk., 2019) for the same observational data will be discussed in this work.